An Introduction to Counselling / Fourth Edition - Mc Leod John (Mc Graw Hill Education, 2009)
A definitive introduction to the theory and practice of counselling and therapy. Preface, Acknowledgements, An Introduction to Counselling, The Social and Historical Origins of Counselling, Theory in Counselling: Using Conceptual Tools to Facilitate Understanding and Guide Action, Themes and Issues in the Psychodynamic Approach to Counselling, The Cognitive-Behavioral Approach to Counselling, Theory and Practice of the Person-Centred Approach, Working with Family Systems, Constructivist and Narrative and Collaborative Approaches: Counselling as Conversation, Transactional Analysis: A Comprehensive Theoretical System, Existential Themes in Counselling, Multicultural Counselling, New Horizons in Counselling: Feminist and Philosophical and Expressive and Nature-Based Approaches, Combining Ideas and Methods from Different Approaches: The Challenge of Therapeutic Integration, The Counselling Relationship, The Process of Counselling, Issues of Power and Diversity in Counselling Practice, Virtues and Values and Ethics in Counselling Practice, References, Index.